2017
DOI: 10.5005/jp-journals-10024-2183
|View full text |Cite
|
Sign up to set email alerts
|

Relative Translucency of a Multilayered Ultratranslucent Zirconia Material

Abstract: Aim:The aim of this study was to compare the translucency parameter (TP) of ultratranslucent multilayered (UTML) zirconia according to thickness and layer level. Materials and methods:Rectangles of UTML zirconia with four layers [dentin layer (DEL), first transitional layer (FTL), second transitional layer (STL), and enamel layer (ENL)] and four different thicknesses (0.4, 0.6, 0.8, and 1 mm) were milled from blanks. Digital images were taken in a dark studio against white and black backgrounds under simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…A few studies have investigated the optical properties of monolithic zirconia and especially its TP and CR but the results are very inhomogeneous due to variations in instrumentation, zirconia brand, the thickness of the specimens and parameters evaluated (Table S1 and Table 1) [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. For a comprehensive evaluation of the commercial products included in the following tables, their brand names and respective composition as reported by manufacturers or presented in associated references are presented in Table 1, at the end of the paper.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have investigated the optical properties of monolithic zirconia and especially its TP and CR but the results are very inhomogeneous due to variations in instrumentation, zirconia brand, the thickness of the specimens and parameters evaluated (Table S1 and Table 1) [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. For a comprehensive evaluation of the commercial products included in the following tables, their brand names and respective composition as reported by manufacturers or presented in associated references are presented in Table 1, at the end of the paper.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The effect of hydrothermal treatment of translucent monolithic zirconia on the light transmission was investigated only in a few studies [49,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67]. A statistically significant decrease or an increase of Tt% over aging time was recorded by Putra et al [49] dependent on the commercial product.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The translucency of different layers of 5Y-ZP showed no significant difference in the previous studies, 21,22 but the studies measured the TP to evaluate translucency. However, the translucency was significantly different between layers based on T t %.…”
Section: Discussionmentioning
confidence: 64%
“…It is important to find out the difference of layers in 5Y-ZP but few studies have compared flexural strength and translucency between layers of 5Y-ZP. 21,22 Despite the shade of 5Y-ZP matches the classical shade guide, additional external staining is essential because the shade of natural teeth is variable. The manufacturers recommend firing under 900°C, but the effect of additional firing on 5Y-ZP is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest ΔE was related to incisal regions (1.58); this might be due to the presence of lower dye components in the incisal layer and different degrees of translucency across the layers. 32 Ueda et al revealed that different layers of UTML disc have different transmittance values. 33…”
Section: Discussionmentioning
confidence: 99%